Erectile dysfunction in patient with obstructive sleep apnea: effects of continuous positive airway pressure - Hyeyun Kim; Keun Tae Kim; Won Chul Shin; Kwang Ik Yang; Ji Yong Ha; Yong Won Cho (The Aging Male)
Background Obstructive sleep apnea (OSA) is linked to various health complications, including erectile dysfunction (ED), which is more prevalent in individuals with OSA. This study explored ED in Korean OSA patients and assessed the impact of continuous positive airway pressure (CPAP) therapy on ED.Methods A total of 87 male patients with OSA from four different sleep centers underwent physical measurements and completed sleep and mental health (MH) questionnaires, including the Korean version of the International index of erectile function (IIEF), before and three months after initiating CPAP therapy.Results After three months of CPAP therapy, the patients demonstrated a significant improvement in ED as measured on the IIEF. However, the study found no significant correlation between the duration of CPAP use and the improvement in IIEF score. It did identify the SF36 quality of life assessment as a significant factor influencing ED improvement after CPAP.Conclusions ED is a prevalent issue that escalates with age and is associated with OSA. CPAP therapy has shown potential in alleviating ED symptoms, particularly in those with underlying psychological conditions, although further research is required to confirm these findings and understand the underlying mechanisms.